Tantangan dan Strategi Kurikulum di Era Digital: Studi Literatur untuk Inovasi Pendidikan - Ibrahim Ibrahim; Nadia Jannah; Dita Febriana Sari; Shobira Afifah (CV. Ulil Albab Corp, 2026)
Digital transformation has reshaped education, demanding adaptive curricula that integrate 21st-century competencies amid challenges like low teacher digital literacy and infrastructure gaps. This study aims to analyze challenges and strategies in digital-era curriculum development through systematic literature review (SLR) for educational innovation. Qualitative research employed SLR methodology, targeting journal articles indexed in Garuda portal as population, with purposive sampling of SINTA 2 articles (2023-2025) on digital curriculum. Instruments included search keywords via Boolean operators; data analysis used thematic analysis and CASP quality appraisal. Findings reveal multidimensional challenges including educator competency deficits, infrastructure disparities, change resistance, and value preservation issues, countered by strategies like systematic technology integration, project-based learning for 21st-century skills, and IT-based curriculum management. In conclusion, comprehensive policy support and stakeholder collaboration enable inclusive digital curricula enhancing educational quality.